2018
DOI: 10.1038/s12276-018-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 5-HT2A receptor function and blockade of Kv1.5 by MK801 and ketamine: implications for PCP derivative-induced disease models

Abstract: MK801 and ketamine, which are phencyclidine (PCP) derivative N-methyl-d-aspartate receptor (NMDAr) blockers, reportedly enhance the function of 5-hydroxytryptamine (HT)-2A receptors (5-HT2ARs). Both are believed to directly affect the pathogenesis of schizophrenia, as well as hypertension. 5-HT2AR signaling involves the inhibition of Kv conductance. This study investigated the interaction of these drugs with Kv1.5, which plays important roles in 5-HT2AR signaling and in regulating the excitability of the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The Institutional Animal Care and Use Committee of Konkuk University approved this study. Mesenteric arterial rings and aortic rings were prepared as previously described 19,20 . The carotid arteries of male Sprague - Dawley rats (10 to 11 weeks old) were cut to exsanguinate the rats under deep ketamine-xylazine anesthesia or after exposure to 100% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Institutional Animal Care and Use Committee of Konkuk University approved this study. Mesenteric arterial rings and aortic rings were prepared as previously described 19,20 . The carotid arteries of male Sprague - Dawley rats (10 to 11 weeks old) were cut to exsanguinate the rats under deep ketamine-xylazine anesthesia or after exposure to 100% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…The isometric tension of arterial rings was measured as previously described 19,20 . The arterial rings were mounted vertically onto two L-shaped stainless steel wires in a 3-mL tissue chamber.…”
Section: Methodsmentioning
confidence: 99%
“…We have placed significant emphasis on the 5-HT2AR system throughout this paper, but it should be acknowledged that some prefer to extend the definition of psychedelics beyond action at this particular receptor. MDMA ( Siegel, 1986 ) and ketamine ( Bowdle et al, 1998 ) are two relevant examples in this regard ( Kuypers et al, 2018 ; Lin et al, 2018 ; Schmid et al., 2014 , Szlachta et al, 2017 ). Like the classic psychedelics, MDMA and ketamine have both been used as adjuncts to psychotherapy, with notable success ( McGirr et al, 2017 ; Sessa et al, 2019 ; Wilkinson et al, 2017 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Previous reports demonstrated that the acute administration of ketamine, which shows rapid antidepressant effects, 47 , 48 enhances the 5-HT level in the prefrontal cortex 49–54 and the hippocampus. 55 Because ketamine is reported to suppress Kv channels, 56 , 57 we assumed that it enhances the spike firing of 5-HT neurons by blocking DTX-I-sensitive Kv1 channels. Bath-applied ketamine hydrochloride enhanced the spike firing in naïve rats ( Fig.…”
Section: Resultsmentioning
confidence: 99%